АЛГОРИТМЫ РАСПОЗНАВАНИЯ И КЛАССИФИКАЦИИ ОСНОВАННЫЕ НА ВЫЧИСЛЕНИИ ОЦЕНОК. - АБДУКАРИМОВ АБДУМАНАП, (TADQIQOTLAR, 2026)
Abstract: To “invent” new methods for solving artificial intelligence problems, the article proposes a method based on an algorithm for calculating estimates. Since among the methods under consideration, the potential of algorithms for calculating estimates is enormous, since it contains the theoretical foundations for reducing the complexity of data processing on large datasets.